Analisis Tingkat Penerimaan Pengguna Terhadap Fitur-Fitur Facebook Untuk E-Commerce - Nabila Payapo; Lana Sularto (LPPM Sekolah Tinggi Teknologi Indonesia Tanjung Pinang, 2019)
The purpose of this study is to find out and explain Facebook users' responses to e-commerce activities from four sides, namely perceived ease of use, the perceived attitude of use, behavioral problems to use, and the real conditions of using the Facebook system for e-commerce activities in Ambon city. The population in this study were Ambon city residents and 30 people were selected as the study sample. From the results of the analysis obtained the average value of achievement scores for the four sides tested were 83%, 81%, 79%, and 76%, so it can be concluded that the perception of ease of use has a significant positive effect on the attitude of use, then attitudes usage has a significant positive effect on behavior to use, and behavior to use has a significant positive effect on the real conditions of the Facebook system usage.